Feminist exploratory interpretive study of the content policy changes of Meta and the corresponding news coverage - Asardag, Dilara (Frontiers in Communication, 2025)
Meta CEO Mark Zuckerberg recently made an announcement that there will be major changes to his company’s content moderation policies. As part of this move, Meta is eliminating its third-party fact-checking program, and replacing it with a community based program called Community Notes as well as making changes to the “Hateful Conduct” policy document of Meta. Under conditions of rising anti-gender backlash and the emergence of post-truth societies transnationally with distorted notions of truth, these changes are deeply concerning for social media researchers, media studies researchers, gender studies researchers and policy scholars as well, as not only CEOs like Mark Zuckerberg but also, politicians like vice-president JD Vance, can be seen as launching a brutal ideological assault on Europe. Taking into account these political dynamics, in this article, I investigated (i) how are the proposed policy changes of Meta discursively constructed in major European online news outlets; (ii) what are the actual policy changes, taking into account women and LGBTIQ+ identities? (iii) what should/ could be the European level response to this situation considering policy and civil society level discussions? I carried out an exploratory reflexive thematic-discursive analysis of 14 articles from major European news sources published online between 7 January to 7 March 2025 related to the announcements of Mark Zuckerberg as well as responses to these announcements and Meta’s official “Hateful Conduct” policy document and the official statement. Adopting an intersectional feminist standpoint theory, strong objectivity and group oppression theory, the exploratory reflexive thematic-discursive analysis was carried out through the lens of hateful speech. The emerging themes of this research are (i) retreat on human rights, LGBTIQ+ rights and freedom of expression, (ii) frightening developments for the rise of misinformation/ disinformation, (iii) Zuckerberg as “re-setting relations with Europe, ignoring Digital Services Act of EU and the need to debunk ´institutionalization of censorship claims.”